การพัฒนาฟิล์มพอลิไดแอเซทิลีน/ซิงก์ออกไซด์/ยางธรรมชาตินาโนคอมพอสิตเป็นตัวรับรู้อุณหภูมิ - อันภิชา พวงสุวรรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The objective of this study was to develop the suitable curing for preparing poly(PCDA)/ZnO/rubber nanocomposites film with practical tensile strength and solvent resistance but still possessing thermochromic response. For sulfur curing system, it was found that amount of accelerator TBzTD and curing temperature and time played an important role on the degree of curing. When curing at 100 oC for 3 hours and adding 2 and 4 phr of TBzTD for NR and ENR film, the rubber film with highest tensile strength and solvent resistance can be obtained.  For poly(PCDA)/ZnO/rubber nanocomposites films prepared by the above condition, the films still showed blue color similar to the pure poly(PCDA)/ZnO nanocomposites but slightly opaque. UV-vis absorption spectrum of poly(PCDA)/ZnO nanocomposites embedded inside the rubber matrix were similar to those of pure one. When poly(PCDA)/ZnO/rubber nanocomposite films prepared NR and ENR solution were heated, the initial thermochromic responsewas observed at 80 oC which was 20 oC higher than the pure poly(PCDA)/ZnO nanocomposites. However, the inreversibility in color transition was unobviously different. For electron beam curing system, it was found that the obtained films had higher tensile strength and solvent resistance than the ones obtained by sulfur curing. For rubber films prepared from the solution without adding any chemical, the optimum curing condition was EB radiating at 250 kGy then heating at 50 oC for 1 hour. For rubber films prepared from the compounded NR latex, the optimum curing condition was EB radiating at 20 kGy then heating at 50 oC for 1 hour.  Both poly(PCDA)/ZnO/NR and poly(PCDA)/ZnO/ENR nanocomposite films from the solutions also showed the initial thermochromic responseat 80 oC.  However, poly(PCDA)/ZnO/NR nanocomposite films from the compounded latex showed the initial thermochromic responseat 60 oC. Even though the films from compounded latex gave highest tensile strength, when heating up to 75 oC and above, their color changed permanently. Therefore, from this study it was suggested that to prepare poly(PCDA)/ZnO/rubber nanocomposites films for using as a thermochromic sensing film, the curing by EB radiation was superior to the sulfur curing. This was because the film cab be formed without adding any chemical, giving clear blur color film. Moreover, poly(PCDA)/ZnO/rubber nanocomposite films had highest strength and solvent resistance.